SUB CHRONIC TOXICITY OF UPPU CHENDURAM -II -ASIDDHA HERBOMINERAL FORMULATION IN WISTAR RAT MODELS - Bhuvaneshwari Thirumalaivelu; Subash Chandran G; Kullappan Shanmugam Uma (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Among the various toxicity tests conducted, Sub-chronic toxicity studies play a crucial role in assessing the long-term health effects of these substances. Sub-chronic testing provides valuable insights into the immediate or short-term effects of a substance, and the consequences of exposure. While Uppu Chenduram II has been prescribed in classical Siddha text since time immemorial for acid peptic disease it lacks scientifc data on its safety concerns. Since this medicine requires to be taken atleast for 30-90 days, the testing for subchronic toxicity becomes crucial to evidence its safety Therefore the present study aimed to detect the non-observed-adverse-effect level (NOAEL) in sub chronic oral toxicity study of Siddha preparation Uppu chenduram-II (UC-II) in Wistar rats. Experimental animals were divided into four groups of 5 rats were placed in cages. Groupt-1 served as control (i.e. the rats were fed without UC-II), then the groups II to IV were daily fed by oral administration of Siddha preparation Uppu chenduram-II at different doses (200, 400 & 600 mg/kg) for 90 days after which the subchronic toxicity profiling was determined. The study results revealed that Uppu chenduram-II caused no adverse effect in any of the tested parameters and the histopathological investigations of the vital organs also produce any toxic changes confirming the safety of the Siddha preparation Uppu chenduram-II at a dose of (200,400 and 600 mg/kg) in the vital organs.